The Occurrence of Pangasius polyuranodon Bleeker, 1852 (Teleostei: Pangasiidae) in Peninsular Malaysia with Remarks on the Comparative Morphology with Pseudolais micronemus (Bleeker, 1847) - Haslawati Baharuddin,; Mohamed Rizman-Idid,; Sekaran Muniandy,; Mohd Zakaria-Ismail, (Universiti Kebangsaan Malaysia, 2014)
This paper presents the first reliable record on the occurrence of the pangasiid catfish, Pangasius polyuranodon, in Peninsular Malaysia. It was previously unnoticed because of misidentification due to its close morphological appearance to Pseudolais micronemus. Pangasius polyuranodon can be positively distinguished from P. micronemus with a combination of characters: Distinctive palatal dentition with a large nearly squared vomerine tooth patch with small lateral palatine toothplates; longer maxillary and mandibular barbels; higher count of anal fin rays; higher counts of gill rakers on the first gill arch. Other characters are: longer caudal peduncle 19.84 ± 24.27% vs 18.35 ± 1.57% standard length (SL); wider anterior snout 35.49-40.60% head length (HL) and wider mouth 45.15-59.65% HL. This finding has important implications for taxonomy and conservation of indigenous Pangasiid catfishes, due to its close morphological appearance to the more abundant P. micronemus but with different biology and ecological behavior, thus necessitating different management and conservation strategies.